Persistent motor system abnormalities in formerly concussed athletes - de Beaumont, L.; Mongeon, D.; Tremblay, S.; Messier, J.; Prince, F.; Leclerc, S.; Lassonde, M.; Théoret, H. (Journal of Athletic Training, 2011)
Context: The known detrimental effects of sport concussions on motor system function include balance problems, slowed motor execution, and abnormal motor cortex excitability.